2017
DOI: 10.1017/s1751731116002160
|View full text |Cite
|
Sign up to set email alerts
|

Perches and elevated platforms in commercial broiler farms: use and effect on walking ability, incidence of tibial dyschondroplasia and bone mineral content

Abstract: Modern fast-growing broilers spend excessive periods resting and their activity further decreases with age. Inactivity has been suggested to increase impaired gait and the incidence of leg disorders. Tibial dyschondroplasia (TD) is a common leg pathology in broilers. A more complex environment might facilitate more activity and improve leg health. Perches or elevated platforms bring variety to broilers' environment and could motivate more locomotion. This study examined the impact of perches and elevated platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 32 publications
8
77
0
Order By: Relevance
“…Earlier studies already indicated that walking ability degenerates as birds grow older (Weeks et al, 2000;Bailie et al, 2013;Kaukonen et al, 2017), in addition, their behavioural activity dwindles and the latency to lie gets shorter (Norring et al, 2016;Bailie et al, 2013). This study further confirmed these findings of progressive immobility when birds became older as they were lying for longer episodes and had fewer bouts of walking.…”
Section: Discussionsupporting
confidence: 87%
“…Earlier studies already indicated that walking ability degenerates as birds grow older (Weeks et al, 2000;Bailie et al, 2013;Kaukonen et al, 2017), in addition, their behavioural activity dwindles and the latency to lie gets shorter (Norring et al, 2016;Bailie et al, 2013). This study further confirmed these findings of progressive immobility when birds became older as they were lying for longer episodes and had fewer bouts of walking.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of tibial dyschondroplasia (TD) and white striping was higher compared to other studies 31,55,56 . For TD, the results are in line with a previous study that found a numerically higher occurrence in birds housed at 10 birds/m 2 , a similar stocking density as in the current study, compared to densities of 15 or 20 birds/m 2 , though the cause for this was unclear 57 .…”
Section: Measure Control A5-s4 A5-s7 A10-s4 A10-tb Sem F-statistic Anmentioning
confidence: 58%
“…Broilers are motivated to perch, but use perches rarely after the age of four weeks (Pettit-Riley & Estevez, 2001;Ventura et al, 2012). Their increased breast muscles have shifted the centre of gravity forward, which makes jumping and balance on perches difficult (Kaukonen et al, 2017). In the present study, broilers in all study groups perched rarely from the third week onwards.…”
Section: Figurementioning
confidence: 60%
“…The results can serve as recommendations for production conditions, although additional studies are suggested to investigate the mutual effects of various types of litter (Avdalovic et al, 2017;Kheravii et al, 2017), stocking densities and environmental enrichment (platforms, ramps, and outdoor access (ICFAW, 2009;Zhao et al, 2014;Norring et al, 2016;Kaukonen et al, 2017) on the occurrence of contact dermatitis and other health, behavioural and production indicators in broilers.…”
Section: Figurementioning
confidence: 99%